2022
DOI: 10.1017/s0030605320001210
|View full text |Cite
|
Sign up to set email alerts
|

Global challenges and priorities for interventions addressing illegal harvest, use and trade of marine turtles

Abstract: Worldwide, conservation initiatives have attempted to curb illegal harvest, use and trade of marine turtles at least since the 1950s. Despite some declines in local trade and consumption, these illegal activities are still often reported as a key threat to marine turtle populations. Reassessing and refining global conservation priorities for marine turtles allows us to formulate evidence-based strategies and effective interventions to address this threat. We surveyed a total of 103 marine turtle conservation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Moreover, an evaluation of the conservation status of all marine turtle Regional Management Units (RMUs) globally revealed that exploitation was scored as the threat category with the second highest impact to marine turtle RMUs, behind only fisheries bycatch (Wallace et al, 2011). Assessing the magnitude, impacts, and trends of illegal exploitation would therefore improve our understanding of the drivers of population changes at both regional and global scales (Lopes et al, 2022), while helping researchers and resource managers identify conservation priorities across geographies, species, and populations. Nevertheless, such an assessment has yet to be conducted on a global scale.…”
Section: Endangered Species Act Convention On International Trade Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, an evaluation of the conservation status of all marine turtle Regional Management Units (RMUs) globally revealed that exploitation was scored as the threat category with the second highest impact to marine turtle RMUs, behind only fisheries bycatch (Wallace et al, 2011). Assessing the magnitude, impacts, and trends of illegal exploitation would therefore improve our understanding of the drivers of population changes at both regional and global scales (Lopes et al, 2022), while helping researchers and resource managers identify conservation priorities across geographies, species, and populations. Nevertheless, such an assessment has yet to be conducted on a global scale.…”
Section: Endangered Species Act Convention On International Trade Inmentioning
confidence: 99%
“…Today, while catch and utilization of marine turtles are still permitted in some parts of the world (see Humber et al, 2014), most countries have regulations that range from full protection (typically with permitted incidental take in commercial fisheries) to regulated take regimes (Brautigam & Eckert, 2006;CITES Secretariat, 2019;Humber et al, 2014;Lopes et al, 2022;Maison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robust consideration of human dimensions has often been highlighted as a critical element for the success of sea turtle conservation due to the high degree of overlap between critical sea turtle habitats and human activities (Davenport and Davenport 2006), as well as the cultural and economic importance of sea turtle by-products (Liles et al 2015, Rojas-Canizales et al 2022. Sea turtle harvesting for human consumption is still considered a primary threat in many regions of the world (Senko et al 2022), and illegal supply of sea turtle by-products is still a reality in local, regional and international markets (CITES 2019, Lopes et al 2022). Despite the limited incorporation of social sciences in sea turtle conservation to understand threats and adopt sound management practices co-developed with relevant stakeholders (Godley et al 2020), progress is being made, and increasing attention to interdisciplinary applications in sea turtle conservation is delivering insightful results (e.g.…”
Section: Introductionmentioning
confidence: 99%